2006
DOI: 10.1042/ba20050172
|View full text |Cite
|
Sign up to set email alerts
|

Application of random amplified polymorphic DNA (RAPD) to detect the genotoxic effect of heavy metals

Abstract: This paper presents the results of a study on the influence of lead, copper, manganese and cadmium on DNA integrity in plant cells. Plants, as biological indicators, can measure the potential effects of pollutants when they are used to measure effects of heavy metals. The genotoxicity of heavy metals in kidney-bean (Phaseolus vulgaris) seedlings was subjected to RAPD (random amplified polymorphic DNA) analysis. An RAPD 'fingerprinting' technique was used to detect DNA damage in the kidney-bean seedlings treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 50 publications
9
77
0
Order By: Relevance
“…This variable correlations can be explained by a range of influencing factors, including the diversity among samples, variable reaction kinetics, presence and activity of enzymes responsible for mediating oxidative stress, (Jaio and Wang 2000;Wu et al 2004;Ozgen et al 2006) and etc. In the samples treated with Ni and Cd as non-redox metals, correspondingly to previously published facts we detected high levels of (Enan 2006;Kekec et al 2010;Cenkci et al 2009). The RAPD, PCR based assay described here is fast, reliable, and easy to conduct in any laboratory for assessment of environmental hazardous metals on plants.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This variable correlations can be explained by a range of influencing factors, including the diversity among samples, variable reaction kinetics, presence and activity of enzymes responsible for mediating oxidative stress, (Jaio and Wang 2000;Wu et al 2004;Ozgen et al 2006) and etc. In the samples treated with Ni and Cd as non-redox metals, correspondingly to previously published facts we detected high levels of (Enan 2006;Kekec et al 2010;Cenkci et al 2009). The RAPD, PCR based assay described here is fast, reliable, and easy to conduct in any laboratory for assessment of environmental hazardous metals on plants.…”
Section: Resultssupporting
confidence: 87%
“…This plant is exposed to heavy metals in its natural environment as a result of various human activities. Bean is a diploid (2n=22) and it has been widely used in physiological and molecular analysis in toxicology (Enan 2006;Kekec et al 2010). Seeds were surface-sterilized with 75 % (v/v) ethanol for 5 min, followed by 10 % (m/v) sodium hypochlorite for 10 min.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAPD analysis have been reported as more sensitive test than classic genotoxic tests since it was capable of detecting temporary DNA changes that may not finally manifest themselves as mutations (Labra et al, 2003;Liu et al, 2007). The present results of Cd exposure in barley seedlings are consistent with the earlier studies on other organisms (Enan, 2006;Liu et al, 2007;Cambier et al, 2010).…”
Section: Endpoint Sensitivitysupporting
confidence: 82%
“…Recently, several selective and sensitive assays developed, such as restriction fragment length polymorphism, quantitative traits loci, random amplified polymorphic DNA (RAPD), amplified fragment length polymorphisms, simple sequence repeat, variable number of tandem repeats for DNA analysis in ecogenotoxicology as a result of the advances in molecular biology 9 . RAPD-PCR is one of the most feasible methods or techniques used for detection of DNA damage and mutations comparing DNA fingerprints from untreated and treated samples 10,11 . Previous studies have shown the biochemical and biological effect of gamma radiation doses (100 and 150 Gray) on F1 adult male and female almond moths, Ephestia cautella (Walker) (Pyralidae: Lepidoptera) descendant of irradiated parental male pupae 12 , and the variation induced in elemental contents in the body tissues of Galleria mellonella adult males and females parents irradiated with 50 and 150 Gy and their F1 generation 13 .…”
Section: Introductionmentioning
confidence: 99%